Risk of transmission of COVID-19 virus infection from asymptomatic COVID-19 positive pregnant patients to Obs/Gynae surgical team - Sheherzad Sohail, Lubna Raiz Dar, Maryam Ishfaq (Journal of Rawalpindi Medical College, 2021)
ABSTRACT Background: Covid 19 is highly contagious disease and Health care workers are always at risk because they are involved in care of suspected, asymptomatic and confirmed cases. It is worthwhile to adopt all practices for prevention of the disease, so they will be able to continue their duties without fear and stress of carrying infection. OBJECTIVE: To determine the number of health care workers who became Covid positive after performing caesarian sections or normal vaginal deliveries of Covid positive asymptomatic cases. Material and Methods: This study was conducted in Gynae/Obs department Of Shalamar Hospital Lahore from March 2020 to September 2020.All the health workers involved in surgeries and deliveries of Covid positive patients were included and they were asked to fill the proforma related to their exposure and development of any signs and symptoms of COVID-19 during the period of fourteen days after exposure. Findings were summarized and analyzed by using SPSS VERSION 22. Results: Total twenty patients who were Covid positive were delivered during this period. Sixty health care workers were involved in their care. During study period three health care workers one doctor and two staff nurses became Covid positive. These infected health care workers were not involved in surgery or delivery of these 20 Covid positive patients. Conclusion: If all the health care workers takes all corona precautionary measures while performing deliveries and C-sections of Covid positive patients risk of transmission to the surgical team can be reduced. Keywords: Covid-19, Health care workers